Endogenous Sterol Synthesis Is Dispensable for Trypanosoma cruzi Epimastigote Growth but Not Stress Tolerance - Dumoulin, Peter C.; Vollrath, Joshua; Won, Madalyn M.; Wang, Jennifer X.; Burleigh, Barbara A. (Frontiers in Microbiology, 2022)
In addition to scavenging exogenous cholesterol, the parasitic kinetoplastid Trypanosoma cruzi can endogenously synthesize sterols. Similar to fungal species, T. cruzi synthesizes ergostane type sterols and is sensitive to a class of azole inhibitors of ergosterol biosynthesis that target the enzyme lanosterol 14α-demethylase (CYP51). In the related kinetoplastid parasite Leishmania donovani, CYP51 is essential, yet in Leishmania major, the cognate enzyme is dispensable for growth; but not heat resistance. The essentiality of CYP51 and the specific role of ergostane-type sterol products in T. cruzi has not been established. To better understand the importance of this pathway, we have disrupted the CYP51 gene in T. cruzi epimastigotes (ΔCYP51). Disruption of CYP51 leads to accumulation of 14-methylated sterols and a concurrent absence of the final sterol product ergosterol. While ΔCYP51 epimastigotes have slowed proliferation compared to wild type parasites, the enzyme is not required for growth; however, ΔCYP51 epimastigotes exhibit sensitivity to elevated temperature, an elevated mitochondrial membrane potential and fail to establish growth as intracellular amastigotes in vitro. Further genetic disruption of squalene epoxidase (ΔSQLE) results in the absence of all endogenous sterols and sterol auxotrophy, yet failed to rescue tolerance to stress in ΔCYP51 parasites, suggesting the loss of ergosterol and not accumulation of 14-methylated sterols modulates stress tolerance.